Dietary Inadequacy of Micronutrients in Adolescent Girls of Urban Varanasi: Call for Action - Krishna, Jaya; Mishra, C.P. (Journal of Nutritional Therapeutics, 2016)
Background: Adolescent girls are vulnerable to dietary inadequacy in general and micronutrients (viz, Iron, Calcium, Vitamin A and C etc) inadequacy in particular due to variety of reasons including their own food preferences. Lack of protective foods in their diet can have serious consequences. Objective: To assess dietary inadequacy of micronutrients in urban adolescent girls and to pinpoint their correlates. Methodology: A community based cross sectional study was undertaken on 400 adolescent girls (10-19 years) of urban Varanasi, selected by adopting multistage sampling technique. Their socio-demographic and personal characteristics were obtained by interviewing parents or other responsible family member. Dietary intake of subjects was assessed by 24 hours recall oral questionnaire method and their micronutrients intake was computed by using nutritive value of Indian foods. Result: In case of 72.8%, 71.2%, 88.2% and 6.2% subjects calcium, iron, Vitamin A and Vitamin C intakes were <50% of Recommended Dietary Allowances. Taking 10-14 years as reference risk of less iron intake was more (AOR; 3.66 CI: 1.30-10.30) in subjects aged 18-19 years. When Scheduled Caste was taken as reference category, risk of less iron intake was more in subjects from other caste category (AOR; 2.91, CI: 1.07-7.91). In comparison to subjects having sibling <4 risk of less calcium intake was more (AOR; 4.37 CI: 1.10-17.39) in subjects having sibling >7.With reference to vegetarians, odds of less vitamin C intake was more in nonvegetarian (AOR=2.01: CI-1.10-3.65) and eggitarian (AOR=2.53: CI-1.03-6.19). Conclusion: Micronutrients deficiency in urban adolescents is quiet predominant and calls for community based interventions to streamline micronutrients supplementation and therapeutic strategies.